2010
DOI: 10.1177/070674371005500905
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Correlates of Gambling Problems in Outpatients with Major Depressive Disorder and Bipolar Disorder

Abstract: These results reaffirm a higher prevalence of gambling both in BD and in MDD populations, compared with previously published community samples. Our study also identifies risk factors for gambling behaviours within these populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 18 publications
(12 reference statements)
4
38
1
Order By: Relevance
“…This finding confirms results from previous studies that showed psychological distress to highly increase the risk of screening positive for problem gambling [45,54,44], and studies demonstrating high rates of psychiatric comorbidity in problem gambling [2,[9][10][11]. Research on the temporality of problem gambling and mood disorders have found that 70% of participants reported their disorder to precede the development of their gambling problems, and a proposed explanation for the association is that maladaptive coping strategies are employed by using excessive gambling as a method of escape from symptoms [55,56,57]. These findings tie into the well-established 'pathways model' of problem gambling in terms of the 'emotionally vulnerable problem gambler', as this predictive sub-type is proposed to be a manifestation of poor coping and problem-solving skills that ultimately uses gambling as an emotional escape from premorbid disorders [58,59].…”
Section: Mental Healthsupporting
confidence: 82%
“…This finding confirms results from previous studies that showed psychological distress to highly increase the risk of screening positive for problem gambling [45,54,44], and studies demonstrating high rates of psychiatric comorbidity in problem gambling [2,[9][10][11]. Research on the temporality of problem gambling and mood disorders have found that 70% of participants reported their disorder to precede the development of their gambling problems, and a proposed explanation for the association is that maladaptive coping strategies are employed by using excessive gambling as a method of escape from symptoms [55,56,57]. These findings tie into the well-established 'pathways model' of problem gambling in terms of the 'emotionally vulnerable problem gambler', as this predictive sub-type is proposed to be a manifestation of poor coping and problem-solving skills that ultimately uses gambling as an emotional escape from premorbid disorders [58,59].…”
Section: Mental Healthsupporting
confidence: 82%
“…These estimates are towards the lower end of comparable figures from two prior studies of smaller samples of patients in treatment services [13,14], but are elevated relative to the general population (the rate of lifetime problem gambling in the total NESARC sample was 1.4%, 95% CI = 1.2-1.5%). There were higher levels of gambling problems when considered across a spectrum of severity, with around 9% of all respondents demonstrating a history of at least some problems with gambling, including low-severity problems (i.e., 'at-risk' gambling).…”
Section: Discussionmentioning
confidence: 55%
“…They indicated rates of gambling problems among patients with PROBLEM GAMBLING IN AFFECTIVE DISORDERS 2 depression that range from 5-13%, with variablity observed across studies, measurement scales, and levels of problem severity. Comparable estimates in bipolar disorder extend from 3-12% [13,14]. These studies indicate associations with clinical outcomes including severity of mood disorders and suicide risk.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Problem gambling has been associated consistently with a range of comorbid mental health disorders, including personality disorders, mood disorders and alcohol and other drug use disorders . Moreover, there is growing evidence to suggest that people with gambling problems are over‐represented within mental health populations, with rates of life‐time or current problem gambling (including pathological gambling) ranging from 0.9 to 43.4% across various substance use and mental health populations . The presence of problem gambling complicates the clinical profile of mental health patients, as it is associated with more severe psychiatric symptoms, alcohol and drug use problems, interpersonal problems, physical health difficulties, cognitive impairment, impulsivity, suicidality, quality of life impairment, social functioning difficulties and financial problems .…”
Section: Introductionmentioning
confidence: 99%